(untitled) (Revista de Ciências Agroveterinárias, 2025)
Bees are the main pollinators and are crucial for many agricultural crops, as well as contributing to the conservation of biodiversity. Many economically important plants depend on these insects, which contribute to increased fruit and seed production. However, high mortality rates have been recorded worldwide, as well as the disappearance of bees. Among the various causes of mortality, some plant species can be toxic and endanger the lives of these hymenoptera. Thus, this study aimed to record bee deaths on Spathodea flowers (Spathodea campanulata P. Beauv.), given that this plant is present on the public sidewalk in the municipality of São Luiz Gonzaga, RS. For this purpose, ten flowers were collected per sampling occasion between February and May 2024, on the ground, under the canopy of seven trees scattered throughout the urban area. The collected flowers were opened, and the insects inside were identified. Of 220 flowers, 14% had dead bees (32 individuals) distributed across four genera, with jataís (Tetragonisca sp.) being the most abundant with 12 records, followed by Plebeia nigriceps and Scaptotrigona bipunctata (with seven and six individuals, respectively). It is concluded that the spathodea flower contributes to the death of bees in the urban area of São Luiz Gonzaga.